THE ROLE OF THE SPIRIT BAPTISM IN PAULINE ESCHATOLOGY: PERAN BAPTISAN ROH DALAM ESKATOLOGI PAULIN - Jefri Hinna (Jurnal Teologi Amreta (ISSN: 2599-3100))
This paper presents the eschatological view of the Spirit Baptism in Paul’s writing. The Spirit Baptism and eschatology in Paul’s perspective are thoughts that function hand in hand with each other and cannot be separated. In Paul, Spirit Baptism is the fulfilment of the Old Testament promise in which God declares to His people that He will be with (stay among) His people through the pouring out of His Spirit. This promise is understood by His people as the eschatological promise of God. This pouring out of the Spirit upon God’s people should be understood as the doctrine of Spirit Baptism which has eschatological role in Paul’s theology. This paper will emphasize the background of Paul’s understanding of the Spirit Baptism as it relates to the soteriological dimension work of the Holy Spirit.